Multiple-Biomarker Approach in a Commercial Marine Scallop from San Jose gulf (Patagonia, Argentina) for Health Status Assessment - Sturla Lompre, Julieta (2019)
The health status of the commercial Tehuelche scallop Aequipecten tehuelchus from San Román and El Riacho in San José gulf (Patagonia, Argentina) was evaluated through biomarkers widely used in ecotoxicological applications. Natural levels of arsenic (As) and cadmium (Cd) were measured to determine their potential relationships with fluctuations of several oxidative stress biomarkers in the scallop. Oxidative biomarkers, such as catalase (CAT), glutathione S-transferase (GST), superoxide dismutase (SOD), metallothioneins (MT), reactive oxygen species (ROS), α-tocopherol (α-T), and lipid peroxidation (LPO) through thiobarbituric acid reactive substances (TBARS) and lipid radical (LR∙), were measured in gills, digestive gland, and muscle of Tehuelche scallop in winter (August 2015) and summer (January 2016). Levels of As and Cd and of most of the biomarkers (SOD, ROS, TBARS, and LR∙) showed strong seasonal variability in the three tissues. In general, the highest values were recorded in digestive gland. The Integrated Biomarker Response index indicated that the most stressed condition of A. tehuelchus was in summer in San Román. Additionally, the Integrated Biomarker Response index showed a strong relationship among tissues and As and Cd accumulation. This kind of approach could be used as an integrated tool to identify the health status of scallop A. tehuelchus from San José gulf.